PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TIME TOKEN TERHADAP HASIL BELAJAR DAN KETERAMPILAN SOSIAL SISWA - Fatkhiyani, Kiki; Ririn Andriani Kumala Dewi; Istiqomah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to test the effect of the time token type cooperative model on class student learning outcomes and the effect of implementing the time token type cooperative model on students' social skills, as well as to test the increase in students' thematic learning outcomes and social skills after using the time token cooperative learning model. This research uses an experimental method with a True Experimental design using Pretest-Posttest Control Group Design. Research data was collected through written tests and questionnaires. Based on the results of the t test calculation, the sig value is obtained. (2-tailed) = 0.024 < α value = 0.050. So, it can be stated that there is an influence of the time token type cooperative learning model. Meanwhile, calculated using the Mann Whitney test, a sig value was obtained. = 0.000 < α = 0.050. So, there is no significant difference in improvement in social skills between experimental class and control class students. In statistical calculations of student learning outcomes using the N-Gain test, an average N-Gain value of 0.34 was obtained with a moderate interpretation. Thus, there is a significant increase in thematic learning outcomes. Meanwhile, the results of statistical calculations of students' social skills using the N-Gain test, obtained an average N-Gain value of 0.62 with a moderate interpretation. So, there is a significant improvement in students' social skills.